O polimorfismo –251 A/T na região promotora do gene da interleucina 8 e o risco de câncer gástrico: estudo caso-controle - Felipe, Aledson Vitor [UNIFESP] (2010)
Background: Helicobacter pylori infection is associated with gastric cancer (GC) non-cardia, however, only a small proportion of infected people develop this cancer. Studies on specific strains of bacteria showed that the genetic and environmental factors are associated with this carcinogenesis. Interleukin-8 (IL-8) plays an important role in inflammation of the stomach mucosa after infection with H. pylori. Studies have shown that the polymorphism of IL-8 may increase the risk of GC. Objective: To investigate the association between polymorphism of IL-8, infection with H. pylori, lifestyle and risk of GC. Patients and methods: Case-control study done in patients with non-cardia GC compared with healthy subjects in the ratio 1:2, respectively. DNA was extracted from white blood cells, purified and polymorphism analysis was performed by PCR-RFLP and visualized by agarose gel electrophoresis to 5%. Infection with H. pylori was investigated by serum antibodies to H. pylori. Environmental issues such as smoking, alcohol consumption and diet were investigated by questionnaire. Results: A total of 312 individuals was studied, and 208 controls and 104 cancer patients. No significant differences between sex or age between the control group and patients with CG. The proportion of patients infected by H. pylori was similar (p=0.15) between the control group (53.8%) and case (45.2%). Lower frequency of AA genotype was found in the cancer group (p=0.01), however, no difference between alleles A and T. Cigarette smoking (p=0.001), sharp intake of fat (p=0.003) and low intake of vegetables (p=0.02) were more frequent in case group. A multivariate logistic regression analysis demonstrated a higher risk of GC in subjects with the heterozygous genotype AT (OR: 2.28 95% IC 1,16-4,49, p=0.02) and excessive consumption of fat (OR: 1 77 95% CI 1,12-2,92, p = 0.03). Smokers and former smokers also showed increased risk of GC compared to the control group (OR: 1.89 95% CI 1,41-3,11, p=0.01). Conclusions: The presence of the AT genotype is associated with increased risk of GC in about two times. The percentage of patients with GC infected with H. pylori, diagnosed by serum antibody levels was not different from the control group in the population. No correlations between allele frequency and risk of GC. Individuals who consume too much fat, ex-smokers and smokers have a higher risk of GC.